Sharīʿah non-compliant income disclosures and the moral legitimacy strategies of Islamic banks - Che Azmi, Anna; Rosman, Romzie; Omar, Normah (Emerald Publishing Limited, 2021)
Purpose – The purpose of this study is to understand the reasons behind the different patterns of Sharīʿah non-compliant income (SNCI) disclosures amongst Islamic banks and, in particular, the extent to which Islamic banks make SNCI disclosures. The process involved in gaining and maintaining moral legitimacy forms the framework for this study. Design/methodology/approach – Interviews were conducted with managers of Islamic banks involved in the reporting of SNCI in company annual reports. Findings – The interview findings show that Islamic banks prefer to use procedures to gain and enhance moral legitimacy amongst their customers, business partners and staff. The constraints and challenges that Islamic banks face in SNCI reporting make this a popular means of securing moral legitimacy. However, these practices may not lead to enhanced and more communicative SNCI disclosures by Islamic banks. Originality/value – To the best of the authors’ knowledge, this is the first study that explains the motivations behind SNCI reporting by Islamic banks and frames these motivations under the moral legitimacy framework